Management of gastric dilatation/bloat in a rabbit (Journal of Laboratory Animal Science, 2021)
A rabbit doe which was one and half year old and weighing 2.4 Kg was presented to clinic with history of anorexia,  lethargy and constipation. Physical examination revealed difficult breathing, hunched posture, distention of the stom ach and abdomen, head pressing, minimally responsive to any stimuli, slightly pale mucus membranes and rectal  temperature of 99.9 oF. The radiographic examination revealed gas distended gastric shadow with various degrees of  gas filled small or large intestine. After complete clinical examination of rabbit, the condition was diagnosed as gastric  dilatation/bloat in rabbit. The rabbit was treated with needle trocarization, intravenous fluid, antibiotics, analgesic/anti-inflammatory drug and laxative. On day 4 of treatment, she was active and behaving normally so all treatment  was discontinued and she was discharged on same day.
Keywords: Gastric dilatation; bloat; rabbit